What Predicts a Successful Life? A Life-Course Model of Well-Being - Richard Layard; Andrew E. Clark; Francesca Cornaglia; Nattavudh Powdthavee; James Vernoit (Institute for the Study of Labor (IZA), 2013)
If policy-makers care about well-being, they need a recursive model of how adult life-satisfaction is predicted by childhood influences, acting both directly and (indirectly) through adult circumstances. We estimate such a model using the British Cohort Study (1970). The most powerful childhood predictor of adult life-satisfaction is the child's emotional health. Next comes the child's conduct. The least powerful predictor is the child's intellectual development. This has obvious implications for educational policy. Among adult circumstances, family income accounts for only 0.5% of the variance of life-satisfaction. Mental and physical health are much more important.
Keywords: A12; D60; H00; I31; 330; conduct; emotional health; life-course; model; intervention; life-satisfaction; well-being; intellectual performance; success